Information Systems and Technologies to Support Learning Proceedings of EMENA-ISTL 2018 - Rocha, Álvaro; Serrhini, Mohammed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book features a selection of articles from the second edition of the conference Europe Middle East & North Africa Information Systems and Technologies to Support Learning 2018 (EMENA-ISTL'18), held in Fez, Morocco between 25th and 27th October 2018. EMENA-ISTL'18 was a global forum for researchers and practitioners to present and discuss recent findings and innovations, current trends, professional experiences and challenges in information systems & technologies to support learning. The main topics covered are: A) information systems technologies to support education; B) education in science, technology, engineering and Mathematics; C) emerging technologies in education learning innovation in the digital age; D) software systems, architectures, applications and tools; E) multimedia systems and applications; F) computer communications and networks; G) IOT, smart cities and people, wireless, sensor and ad-hoc networks; H) organizational models and information systems and technologies; I) human-computer Interaction; J) computers & security, ethics and data-forensic; K) health informatics, and medical informatics security; l) information and knowledge management; m) big data analytics and applications, intelligent data systems, and machine learning; n) artificial intelligence, high performance computing; o) mobile, embedded and ubiquitous systems; p) language and image processing, computer graphics and vision; and q) the interdisciplinary field of fuzzy logic and data mining.
Metaheuristic Approaches for Solving University Timetabling Problems: A Review and Case Studies from Middle Eastern Universities -- Ontology-based Modeling for a Personalized MOOC Recommender System -- Hybrid Recommendation Approach in Online Learning Environments -- Mobile Learning Oriented Towards Learner Stimulation and Engagement -- Teaching and Learning How to Program Without Writing Code -- Emerging Technologies and Learning Innovation in the New Learning Ecosystem -- Security Scheme for IoT Environments in Smart Grids -- Bitcoin Difficulty, A Security Feature -- Rating Microfinance Products Consumers Using Artificial Neural Networks -- Toward an Evaluation Model for Open Government Data portals -- A New Supervised Learning Based Ontology Matching Approach Using Neural Networks -- Multi-cloud Resources Optimization for Users Applications Execution.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence